Response to “Considering the Potential Benefits of Over-the-Counter Naloxone” by Evoy et al [Letter] - Fuehrlein B (Dove Medical Press, 2021)
Brian Fuehrlein VA Connecticut Healthcare System, West Haven, CT, USACorrespondence: Brian FuehrleinVA Connecticut Healthcare System, West Haven, CT 06516, USAEmail brian.fuehrlein@yale.edu View the original paper by Dr Evoy and colleagues